1994
DOI: 10.3181/00379727-207-43809
|View full text |Cite
|
Sign up to set email alerts
|

Altered Control of Ventilation in Streptozotocin-Induced Diabetic Rats

Abstract: The purposes of this study were (i) to determine if ventilatory control is altered in streptozotocin (STZ)-induced diabetic rats and (ii) to determine whether insulin treatment of diabetic rats could prevent ventilatory abnormalities. Male Sprague-Dawley rats were randomly assigned to three groups: control (n = 10), diabetic (n = 9), and diabetic treated with insulin (n = 9). The diabetic group exhibited a progressive reduction of tidal volume, minute ventilation, and CO2 production compared with the control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
3
19
1
1
Order By: Relevance
“…If the association between PaCO 2 and AHI is intuitable, the independent association between degree of insulin resistance and AHI is more complex to explain and it might be due to the well known direct effect that insulin exerts on central nervous system and thus on respiratory center. 16 Furthermore, the pathophysiological interaction between degree of insulin resistance and circulating soluble leptin receptor concentration on the respiratory center is still a problem and requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the association between PaCO 2 and AHI is intuitable, the independent association between degree of insulin resistance and AHI is more complex to explain and it might be due to the well known direct effect that insulin exerts on central nervous system and thus on respiratory center. 16 Furthermore, the pathophysiological interaction between degree of insulin resistance and circulating soluble leptin receptor concentration on the respiratory center is still a problem and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a regulatory effect of insulin on ventilatory control has been demonstrated in streptozotocin-induced diabetic rats. 16 As far as leptin is concerned, a direct effect of leptin on the respiratory control center in the brain has been demonstrated in the C57BL=6J-Lep ob mouse, which is mutated for the gene encoding leptin. 17 Due to the relationship between SNS activity, ventilatory control and development of SAS, one can hypothesize that both plasma insulin and leptin levels play a role in the development of SAS.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously explored parameters of altered control of ventilation in a STZ rat model of diabetes mellitus. In this four-week study of male SD rats treated with STZ, we observed a progressive reduction of V T , V˙E, andV CO 2 compared to the control group and a STZ diabetic group treated with insulin (STZ/I) (Hein et al, 1994). Hypercapnic (3, 6, 9%) and hypoxic (10%) ventilatory responses were also significantly less in the STZ group than the control group and the STZ/I group.…”
Section: Ventilatory and Metabolic Results In Diabetic Modelsmentioning
confidence: 90%
“…Chemoreceptor reflexes to hypoxia and hypercapnea appears to be altered in diabetic individuals (Williams et al, 1984;Montserrat et al, 1985;Sobotka et al, 1986;Nishimura et al, 1989;Tantucci et al, 1997) and in rats (Hein et al,1994). Although these reflexes may have been depressed in our STZ-treated rats, we do not know what effect this would have in response to capsaicin aerosol challenge.…”
Section: Effect Of Diabetes On Slowly Adapting Pulmonary Stretch Recementioning
confidence: 83%
“…Both variables involve C-fiber function. Also while investigating the control of ventilation Hein et al (1994) determined that the responses to hypercapnia and hypoxia were less in streptozotocin-treated rats than in either control or insulin-treated rats. These studies suggest that sensory neuropathy develops in the STZ-treated rat.…”
Section: Introductionmentioning
confidence: 99%